Optimization of Thesis Guidance to Accelerate Graduation of Public Administration Students at Universitas Mulawarman - Khaerani, Thalita Rifda; Apriani, Fajar; Ardi, Muhammad (Universitas of Muhammadiyah Makassar, 2024)
As the foundation of national education, universities play a major role in forming graduates who are knowledgeable, skilled, competent and skilled. As a study program with A accreditation, the FISIP UNMUL Public Administration Study Program requires students to complete their studies as soon as possible. Students experience obstacles in the thesis guidance process which causes students to graduate not on time. This study aims to analyze and identify the factors of delays in the thesis guidance process of students of the Public Administration Study Program of FISIP UNMUL using the Fishbone diagram and determine the priority of the problem using the USG (Urgency, Seriousness, and Growth) scoring method through a Likert interval scale. The results showed that the problems of delays in the thesis guidance process of students of the Public Administration Study Program of FISIP UNMUL include: Man, students who are passive in the guidance process; Method, there is no new method in the thesis guidance process; Machine, there is no roadmap of research issues for students; Material, thesis writing guidelines that have not been understood by students. The actualization of providing motivation and a thesis writing guide pocket book, coaching clinic activities, making weekly progress reports and issue catalog roadmaps by dividing two concentration classes with the latest issues are efforts to optimize the thesis guidance process of FISIP UNMUL Public Administration students.